The Long-Term Health Impact of Agent Orange: Evidence from the Vietnam War - Duong Trung Le; Thanh Minh Pham; Solomon Polachek (Institute of Labor Economics (IZA), 2021)
This paper examines the long-term health impact of Agent Orange, a toxic military herbicide containing dioxin that was used extensively during the U.S.-Vietnam war in the 1960-70s. Using a nationally representative health survey and an instrumental variable approach that addresses the potential endogeneity in the location and the intensity of U.S. defoliant missions, we report several findings. First, relative to the average prevalence rate of the sample population, we find that Vietnamese civilians located in a commune one-standard-deviation more exposed to herbicide during the war were 19.75 percent more likely to suffer from a health disease medically linked to Agent Orange three decades later. Second, disaggregating by disease types, we observe significant effects on blood pressure disease and mobility disability. Third, across cohorts, we find significant detrimental impact on those born before herbicide missions ended, especially among wartime children, infants, and those in-utero during the 1962-1971 period.
Keywords: N45; I10; Q53; 330; Agent Orange; herbicide; health; conflicts; Vietnam war